Object Detection: Current and Future Directions - Verschae, Rodrigo; Ruiz-del-Solar, Javier (Frontiers in Robotics and AI, 2015)
Object detection is a key ability required by most computer and robot vision systems. The latest research on this area has been making great progress in many directions. In the current manuscript we give an overview of past research on object detection, outline the current main research directions, and discuss open problems and possible future directions.